Sclerosing haemangioma of the lung: A case report - Thapa, R; Lakhey, M; Shrestha, U (Journal of Kathmandu Medical College, 2012)
Sclerosing haemangioma is a rare neoplasm of the lung which behaves in a clinically benign fashion. Herein, a case of sclerosing haemangioma of the lung in a 52 years old woman is reported. She presented with symptoms of cough and chest pain. Chest X-ray and CT scan showed a well-defined lesion in lower lobe of left lung. Bronchoscopic biopsy findings were suggestive of a carcinoid tumor. Later the tumor was removed by lobectomy. The distinctive constellation of histologic findings revealed it to be a sclerosing haemangioma. DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7254 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.33-36